P.226 Variations in and Determinants of Length of Stay at an Academic Spinal Care Center from 2006-2019. (November 2021) - Dandurand, C; Hindi, MN; Ailon, T; Boyd, M; Charest-Morin, R; Dea, N; Dvorak, M; Fisher, C; Kwon, B; Paquette, S; Street, J
Abstract : Background: Length of stay (LOS) is a surrogate for care complexity and a determinant of occupancy and service provision. Our primary goal was to assess changes in and determinants of LOS at a quaternary spinal care center. Secondary goals included identifying opportunities for improvement and determinants of future service planning. Methods: This is a prospective study of patients admitted from 2006 to 2019. Data included demographics, diagnostic category (degenerative, oncology, deformity, trauma, other), LOS (mean, median, interquartile range, standard deviation) and in-hospital adverse events (AEs). Results: 13, 493 admissions were included. Mean age has increased from 48.4 (2006) to 58.1 years (2019) (p=<0.001). Mean age increased overtime for patients treated for deformity (p=<0.001), degenerative pathology (p=<0.001) and trauma (p=<0.001), but not oncology (p=0.702). Overall LOS has not changed over time (p=0.451). LOS increased in patients with degenerative pathology (p=0.019) but not deformity (p=0.411), oncology (p=0.051) or trauma (p=0.582). Emergency admissions increased overtime for degenerative pathologies (p=<0.001). AEs and SSIs have decreased temporally (p=<0.001). Conclusions: This is the first North American study to analyze temporal trends in LOS for spine surgery in an academic center. Understanding temporal trends in LOS and patient epidemiology can provide opportunities for intervention, targeted at the geriatric populations, to reduce LOS.